2002
DOI: 10.1002/jbm.10220
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of functionally graded MgCO3 apatite accelerating osteoblast adhesion

Abstract: As a means of improving the biological properties of materials for use as bone substitutes, functionally graded carbonate apatite containing Mg, FGMgCO3Ap, was synthesized at 60 degrees C and pH 7.4 using a gradient magnesium supply system. X-ray diffraction analysis of FGMgCO3Ap showed a poorly crystallized apatitic pattern, similar to that of human bone. ESCA analysis clearly showed the negative gradient distribution in Mg1s intensity (atomic concentration) of magnesium from the crystal surface toward the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(99 citation statements)
references
References 24 publications
6
93
0
Order By: Relevance
“…that Mg is a promising agent in skeletal tissue engineering applications due to its ability to 16 stimulate new bone formation [23]. Mg was suggested to interact with integrins of osteoblasts 17 that are responsible for cell adhesion and stability [23,50]. The importance of Mg in bone [25,51,52].…”
mentioning
confidence: 99%
“…that Mg is a promising agent in skeletal tissue engineering applications due to its ability to 16 stimulate new bone formation [23]. Mg was suggested to interact with integrins of osteoblasts 17 that are responsible for cell adhesion and stability [23,50]. The importance of Mg in bone [25,51,52].…”
mentioning
confidence: 99%
“…As for Na substitution, Jung et al 17) added sodium nitrate to calcium hydroxide and phosphoric acid to cause a reaction, and as for K substitution, Kannan et al 18) reported K-substitution of HAp by a wet method using potassium nitrate. Li et al 19) reported simultaneous substitution of Na + and CO 3 2¹ ions, and Yamasaki et al 20) reported simultaneous substitution of Mg 2+ and CO 3 2¹ ions. There have been only a few reports, however, in which three or more types of ions have been substituted simultaneously.…”
Section: )5)mentioning
confidence: 99%
“…Mg 2+ ions may contribute to the bone metabolism of osteoclast and osteoblast action with the integrins at Recently, scaffold biomaterials have been studied in the tissue engineering field. In a continuation of those studies, functionally graded CO3apatite containing Mg, producing a negative gradient of magnesium concentration from the surface toward the core, was synthesized 12) . The degree of cell adhesion to a composite that was made by mixing the FGMgCO3apatite and collagen to facilitate bonding and processing was investigated.…”
Section: Functionally Graded Mg-containing Co3ap-collagen Compositementioning
confidence: 99%